2005
DOI: 10.1002/bdrc.20057
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the hypertrophic chondrocyte: Microenvironmental perspectives on apoptosis and survival in the epiphyseal growth plate

Abstract: The goal of this review is to examine the fate of the hypertrophic chondrocyte in the epiphyseal growth plate and consider the impact of the cartilage microenvironment on cell survival and apoptosis. Early investigations pointed to a direct role of the hypertrophic chondrocyte in osteogenesis. The terminally differentiated cells were considered to undergo a dramatic change in shape, size, and phenotype, and assume the characteristics of an osteoblast. While some studies have supported the notion of transdiffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
139
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 83 publications
2
139
1
4
Order By: Relevance
“…Studies showing the presence of apoptotic nuclei in HCs and abundant apoptogens in the microenvironment of HCs at the chondro-osseous junction provided the current concept that death, by apoptosis or extended autophagy, is the fate of HCs in endochondral ossification (12,22). However, these studies cannot preclude that some HCs survive.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Studies showing the presence of apoptotic nuclei in HCs and abundant apoptogens in the microenvironment of HCs at the chondro-osseous junction provided the current concept that death, by apoptosis or extended autophagy, is the fate of HCs in endochondral ossification (12,22). However, these studies cannot preclude that some HCs survive.…”
mentioning
confidence: 97%
“…The possibility that HCs are an alternative source of osteoblasts is controversial (12). Support comes from imaging, morphological, and ultrastructural studies in vivo, in which HCs were observed at the chondro-osseous junction and osteoblasts in chondrocyte lacuna (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the process of cell death, chondrocytes become hypertrophic and terminally differentiated. In addition, with the degradation of extracellular matrices, chondrocytes die and disappear (Shapiro et al, 2005;Sakakura et al, 2007). Compared with the degeneration of Meckel's cartilage, more studies were conducted on endochondral ossification.…”
Section: Introductionmentioning
confidence: 99%
“…1 A reason for considering that the cells exhibit autophagy, is that in the maturing zone of the growth plate, the central core of cells are most removed from oxygen and may be depleted of growth factors and critical nutrients. Some early analytical studies of the growth plate provide evidence in support of this notion.…”
Section: Introductionmentioning
confidence: 99%